METAPHORS OF INCLUSIVE SEMANTICS IN THE LANGUAGE OF SCIENCE - Yaroslava Bedrych (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
Scientific discourse is viewed as a specific object of linguistic analysis in light of cognitive-discursive paradigm. Categories are integral parts of the scientific discourse, yet there is no full list of such categories. Insufficient studies of the category of inclusiveness, as one of the categories that has not come under linguistic scrutiny, specifically, in modern English scientific discourse, call for investigating this category and its elements. The paper deals with the analysis of the metaphors of inclusive semantics to convey the category of inclusiveness. Empirical material of our study involves Anglo-American articles in the field of information and communication technologies, as this research domain deals with the latest cutting-edge technologies that influence virtually all spheres of human life due to the potential of such technologies to dramatically reshape information society in the age of digital revolution. We have outlined the following types of inclusive metaphors in the language of science: the metaphor of CONTAINER that is expressed through a bunch of linguistic devices (nouns: container, envelope, family, house; verbs: to house, to wrap up); the metaphor of CIRCLE (nouns: circle; verbs: to circle, compass, to compass, to encircle, to enclose, to surround, set phrase: to range from...to); and the metaphor of CONTENTS. The obtained results have shown that the metaphor of CONTAINER is the most frequently used one.